Endophytic Beauveria bassiana promotes plant biomass growth and suppresses pathogen damage by directional recruitment - Sui, Li; Lu, Yang; Zhou, Linyan; Li, Nannan; Li, Qiyun; Zhang, Zhengkun (Frontiers in Microbiology, 2023)
Entomopathogenic fungi (EPF) can colonize and establish symbiotic relationships with plants as endophytes. Recently, EPF have been reported to suppress plant pathogens and induce plant resistance to diseases. However, the potential mechanisms via which EPF as endophytes control major plant diseases in situ remain largely unknown. Here, pot and field experiments were conducted to investigate the mechanisms via which an EPF, Beauveria bassiana, colonizes tomato, under Botrytis cinerea infection stress. B. bassiana blastospores were inoculated into tomato plants by root irrigation. Tomato resistance to tomato gray mold caused by B. cinerea was evaluated by artificial inoculation, and B. bassiana colonization in plants and rhizosphere soil under B. cinerea infection stress was evaluated by colony counting and quantitative PCR. Furthermore, the expression levels of three disease resistance-related genes (OXO, CHI, and atpA) in tomato leaves were determined to explore the effect of B. bassiana colonization on plant disease resistance performance in pot experiments. B. bassiana colonization could improve resistance of tomato plants to gray mold caused by B. cinerea. The incidence rate, lesion diameter, and disease index of gray mold decreased in both the pot and field experiments following B. bassiana colonization. B. bassiana was more likely to accumulate in the pathogen infected leaves, while decreasing in the rhizosphere soil, and induced the expression of plant resistance genes, which were up-regulated in leaves. The results indicated that plants could "recruit" B. bassiana from rhizosphere soil to diseased plants as directional effects, which then enhanced plant growth and resistance against pathogens, consequently inhibiting pathogen infection and multiplication in plants. Our findings provide novel insights that enhance our understanding of the roles of EPF during pathogen challenge.